Different Aspects of Congenital Myasthenic Syndromes in Childhood - Aslan, Mahmut; Kırık, Serkan (My University, 2022)
Objective: Congenital myasthenic syndrome (CMS) is a heterogeneous group of diseases that are not immune-mediated. It is caused by structural defects in different synaptic proteins of neuromuscular transmission as a result of different mutations. CMS is classified according to the location of the mutant protein as presynaptic, synaptic basal lamina-associated, or post synaptic. In this study, we aimed to help further the knowledge of this issue by analyzing the clinical features and treatment responses of patients with an extremely rare condition of CMS. Methods: The clinical information of 13 patients who attended the CMS clinic at Mersin City Training and Research Hospital and Aydın Maternity and Child Hospital were reviewed. After considering the clinical diagnosis in all our cases, we performed a genetic diagnosis with whole exon sequencing or a CMS panel. Results: Of the 13 patients included in this study, 11 (84.6%) were males and 2 (15.4%) were females. The mean age of our patients was 73.30±60.56 months, and the mean age at the time of diagnosis was 44±49.15 months. In our patients diagnosed with CMS, 9 (69.2%) COLQ mutations, 2 (15.4%) CHAT mutations, 1 (7.7%) RAPSN mutation, and 1 (7.7%) SCN4A mutation were observed. Ephedrine was started in 8 of the 9 patients with COLQ mutations, and a good response was obtained. A good response to treatment was not ob served in those patients who were started on pyridostigmine. Conclusion: CMS can often be confused with other neuromuscular diseases. In patients presenting with ptosis, bulbar findings, apnea, and muscle weakness, CMS should be prediag nosed, and a genetic examination should be performed on these patients.
Keywords: Nörolojik Bilimler; Pediatri